Perhitungan Harga Pokok Produksi untuk Menetapkan Harga Jual Sei Babi pada Depot Sei Andalan Kota Kupang - Stevanness Sianto; I Komang Arthana; Herly M Oematan (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to determine and compare the application of the full costing method and the variable costing method in calculating the cost of production to determine the selling price of pork sei at the Andalan Bistro, Kupang City. Data collection was carried out using observation, interviews and documentation methods. The data analysis technique used in this research is a comparative descriptive method. The comparative descriptive method is a research method that compares the determination of the cost of production, the cost of production of pork sei (Kg) and the selling price using the full costing method, variable costing method and according to the bistro. Based on the research results, the Andalan Bistro does not apply the full costing method or the variable method. costing in calculating the cost of production, Andalan Bistro uses a simple method of calculation and does not calculate all elements of production costs in calculating the cost of production. Andalan Bistro determines its selling price according to market prices. This can result in the profit that will be obtained not being as expected